A mini‐corer for precision sampling of the water‐sediment interface in subglacial lakes and other remote aqueous environments. (22nd October 2018) - Keen, Peter; Saw, Kevin; Rundle, Nicholas; Brown, Robin; Wyatt, James; Shorter, Stephen; Edwards, Michael; Siegert, Martin; Mowlem, Matthew
Abstract: Recent interest in Antarctic subglacial lakes has seen the development of bespoke systems for sampling them. These systems are considered pristine environments potentially harboring undisturbed sedimentary sequences and ecosystems adapted to these cold oligotrophic environments in the absence of sunlight. The water/sediment interface is considered a prime location for the detection of microbial life and so is of particular interest. This article describes the development of a small corer to capture and retain a short core that includes the water/sediment interface specifically to address the question of whether life exists in these lakes. This apparatus was developed as part of the UK led project to access, measure, and sample subglacial Lake Ellsworth. In addition to addressing the constraints of coring in this difficult environment, the results of subsequent testing suggest that this corer can be applied to sampling sediments in other environments and would be particularly useful in low energy environments when the water‐sediment interface is indistinct or unconsolidated.